Seasonal metabolic depression, substrate utilisation and changes in scaling patterns during the first year cycle of tegu lizards (Tupinambis merianae) - Souza, S. C. R. de; Carvalho, J. E. de; Abe, Augusto Shinya [UNESP]; Bicudo, J. E. P. W.; Bianconcini, M. S. C. (Company of Biologists Ltd, 2004)
The tegus increase in body mass after hatching until early autumn, when the energy intake becomes gradually reduced. Resting rates of oxygen consumption in winter drop to 20% of the values in the active season (Vo(2)=0.0636 ml g(-1) h(-1)) and are nearly temperature insensitive over the range of 17-25degreesC (Q(10)=1.55). During dormancy, plasma glucose levels are 60% lower than those in active animals, while total protein, total lipids and beta-hydroxybutyrate are elevated by 24%, 43% and 113%, respectively. In addition, a significant depletion of liver carbohydrate (50%) and of fat deposited in the visceral fat bodies (24%) and in the tail (25%) and a slight loss of skeletal muscle protein (14%) were measured halfway through the inactive period. Otherwise, glycogen content is increased 4-fold in the brain and 2.3-fold in the heart of dormant lizards, declining by the onset of arousal. During early arousal, the young tegus are still anorexic, although Vo(2) is significantly greater than winter rates. The fat deposits analysed are further reduced (62% and 45%, respectively) and there is a large decrease in tail muscle protein (50%) together with a significant increase in glycogen (2-3-fold) and an increase in plasma glucose (40%), which suggests a role for gluconeogenesis as a supplementary energy source in arousing animals. No change is detectable in citrate synthase activity, but beta-hydroxyacyl CoA dehydrogenase activities are strongly affected by season, reaching a Mold and 5-fold increase in the liver tissue of winter and arousing animals, respectively, and becoming reduced by half in skeletal muscle and heart of winter animals compared with late fall or spring active individuals. From hatching to late autumn, the increase of the fat body mass relatively to body mass is disproportionate (b=1.44), and the mass exponent changes significantly to close to 1.0 during the fasting period. The concomitant shift in the Vo(2) mass exponent in early autumn (b=0.75) to values significantly greater than 1.0 in late autumn and during winter dormancy indicates an allometric effect on the degree of metabolic depression related to the size of the fat stores and suggests greater energy conservation in the smaller young.
Keywords: dormancy; fasting; oxygen consumption; metabolic depression; scaling; lipid; glycogen; HOAD; CS; lizard; tegu; Tupinambis merianae